(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explains the structure of the Latin alphabet, its reading principles, and the role of vowels, consonants, and letter combinations in pronunciation and language development. The Latin alphabet, widely used across many modern languages, consists of 26 letters, categorized into vowels (A,E,I,O,U,) and consonants( the remaining 21 letters). These letters formed the foundation of written communication, influencing word construction, pronunciation, and reading fluency. Vowels are essential for forming syllables, ensuring smooth pronunciation, while consonant provide stability and structure to words. Reading in the Latin alphabet involves phonetic rules that vary by language, affecting how letters and letter combinations are pronounced. Some letter have consistent sounds, while other change based on their position or surrounding letters.